Effectiveness of exercise in reducing symptom burden among hemodialysis patients: a non-pharmacological intervention approach - Alshammari, Bushra; Edison, J. Silvia; Alkubati, Sameer A.; Alrasheeday, Awatif M.; Albagawi, Bander; Alharbi, Laila Lafi; Motakef, Hajer I.; Alshammari, Layla; Siam, Bahia Galal Abd El-Razik; Alharbi, Nawal Abdullah; Assiri, Wejdan; Almoqad, Amirah Abdulaziz; et al. (Frontiers in Public Health, 2025)
BackgroundEnd-stage renal disease (ESRD) patients undergoing hemodialysis (HD) often experience a substantial symptom burden, which negatively impacts their quality of life. While pharmacological treatments are commonly used to manage these symptoms, non-pharmacological interventions, such as exercise, have gained attention for their potential to alleviate both physical and psychological symptoms without additional medication-related side effects. Compared to other strategies that often target a limited range of symptoms—such as meditation for depression or music therapy for anxiety—exercise offers broader benefits, making it particularly promising for patients receiving HD.ObjectiveThis study aimed to evaluate the effectiveness of an exercise intervention in reducing the symptom burden among patients receiving HD in Hail City, Saudi Arabia.MethodsA quasi-experimental pre-post intervention design was employed, involving (n = 72) HD patients recruited through convenience sampling from King Salman Specialist Hospital and King Khalid Hospital. Participants engaged in a structured exercise program for 12 weeks, with sessions conducted three times per week for 30 min. Symptom severity was assessed using the Dialysis Symptom Index (DSI) before and after the intervention. Data were analyzed using paired t-tests, with a significance level set at p < 0.05.ResultsA total of 72 HD patients participated in the study. The exercise intervention led to a statistically significant reduction in overall symptom severity scores, decreasing from 105.94 ± 9.77 pre-intervention to 102.50 ± 9.61 post-intervention (p < 0.001). Significant improvements were noted in multiple symptoms, including constipation (p = 0.002), decreased appetite (p < 0.001), restless legs (p = 0.001), fatigue (p < 0.001), joint pain (p = 0.045), difficulty concentrating (p = 0.045), and several emotional symptoms such as worrying (p = 0.024), nervousness (p = 0.002), trouble sleeping (p < 0.05), and feelings of sadness (p < 0.001). Sociodemographic factors, including younger age, female gender, shorter dialysis duration, and higher comorbidity burden, were significantly associated with greater baseline symptom severity.ConclusionThe findings demonstrate that a structured exercise program is an effective non-pharmacological intervention for reducing symptom burden among HD patients. These results support incorporating exercise into routine HD care to enhance patient well-being. Future initiatives should focus on integrating supervised, accessible exercise programs into dialysis centers to maximize adherence and therapeutic benefit.